PENGARUH PELATIHAN SDM TERHADAP UPAYA MENINGKATKAN PRODUKTIVITAS KERJA APARAT PADA KANTOR DESA MALEO KABUPATEN POHUWATO - Tamsir Tamsir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2016)
The purpose of this study was to determine and analyze the Influence of Human Resource training on the productivity of work forces at the village office Maleo Pohuwato. Based on the results of data processing using SPSS results are obtained the following regression equation: Y = 15.010 + 0,438X. SPSS data processed from the simple regression equation where the constant value of 15.010 and productivity of 0,438 officials were also used as a benchmark. Processed data on SPSS program obtained value of R Square (R2) of 0.540 or 54.00%. While anatara relationship with productivity training apparatus in Maleo village of 0.735 or 73.5%. The processed data using SPSS can be obtained F count amounted to 21 132> sig. 0,000 means that Ho refused and Ha accepted which means a partial contribution to the training of personnel productivity is the amount of 54.00 and relations between them amounted to 0.735 or 73.5% is significant. Contributions of training on productivity in the rural village officials Maleo at 54.00. Therefore it can be concluded that the training variables significantly affect labor productivity in the rural village officials Maleo.